The Management Fund Classification to Determine Reliable Maintenance Fees of High-Rise Residential in Malaysia - Hanum Abd Wahab, Siti Rashidah; Che-Ani, Adi Irfan; Omar, Halizah; Ibrahim, Maznah; Mamat, Maharam (International Journal of Supply Chain Management, 2017)
High-rise residential building is a type of housing that has multi-dwelling units built on the same land. This type of housing has become popular each year in urban area due to the increasing cost of land. Unfortunately, there are several issues occurred in managing high rise residential building especially in maintenance fund. Thus, distribution of maintenance fund need to be clarified in order to make it well organized. The purpose of this paper is to identify the classification of maintenance fund distribution at high rise residential building. The survey was done on 170 high-rise residential schemes within Klang Valley area. The result, there are five classification of maintenance fund allocation identified namely, management fund for administration and utilities, maintenance fund for exclusive facilities, maintenance fund for basic facilities, maintenance fund for support facilities and management sinking fund. Then, all the items in these five factors undergo descriptive analysis to identify the importance of maintenance fund allocation for non-low cost of high rise residential building in Malaysia.